Pengaruh Kepuasan Konsumen dan Kemudahan Terhadap Loyalitas Pelanggan Maxim di Kota Palembang - Pratiwi, Andini Putri; Nurrahmi, Maftuhah; Puspasari, Mardiana (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study is to determine consumer satisfaction and convenience towards Maxim customer loyalty in Palembang City. This type of research uses associative. The research location was conducted in Palembang City with 100 samples. The data used is Primary Data. The data collection method used in this study is Multiple Linear Regression, F Test, t Test and coefficient of determination. The results of the study indicate that consumer satisfaction and convenience have a positive and significant influence on Maxim customer loyalty in Palembang City.